The roles of transition metals in the physiology and pathogenesis of Streptococcus pneumoniae - Honsa, Erin S.; Johnson, Michael D.; Rosch, Jason W. (Frontiers in Cellular and Infection Microbiology, 2013)
For bacterial pathogens whose sole environmental reservoir is the human host, the acquisition of essential nutrients, particularly transition metals, is a critical aspect of survival due to tight sequestration and limitation strategies deployed to curtail pathogen outgrowth. As such, these bacteria have developed diverse, specialized acquisition mechanisms to obtain these metals from the niches of the body in which they reside. To oppose the spread of infection, the human host has evolved multiple mechanisms to counter bacterial invasion, including sequestering essential metals away from bacteria and exposing bacteria to lethal concentrations of metals. Hence, to maintain homeostasis within the host, pathogens must be able to acquire necessary metals from host proteins and to export such metals when concentrations become detrimental. Furthermore, this acquisition and efflux equilibrium must occur in a tissue-specific manner because the concentration of metals varies greatly within the various microenvironments of the human body. In this review, we examine the functional roles of the metal import and export systems of the Gram-positive pathogen Streptococcus pneumoniae in both signaling and pathogenesis.